Growth Cycles and Paleoecology of Devonian Rugosa - Marshall, Michael Cameron (My University, 1984)
Solitary rugose corals of the Middle Devonian Hungry Hollow Formation exhibit annual, synodic month and periodicities of their epithecal growth lines. Annual cyclicity is poorly developed due to the slight seasonal variation of the 33°S paleolatitude. Thirteen monthly bands each with a mean of 30.38 diurnal lines comprise a Middle Devonian year of approximately 395 days. Corallite measurements yielded a monthly vertical growth rate of .377 cm. A major correlative reduction in monthly growth is apparent at approximately seven monthly bands from the apex. Environmental deterioration probably accounts for this reduction and the randomly occurring disturbance lines visible on the epithecae. Random periods of rejuvenescence in which the corallite diameter is reduced may be linked to abnormal environmental conditions. Bryozoan larvae actively settled on corallite areas which provided shelter from abrasion, water currents and light. The growth of the corallites is anisometric and exhibits no apparent relationship between monthly growth rate and diameter increase.
The frequent occurrences of geniculate corallites in the sample are indicative of occasionally turbulent water conditions that toppled the immature corallites. Storms probably created turbulence that toppled much of the coral population with heights of 2.0-4.0 cm and resulted in subsequent geniculation. An exceptionally violent storm probably destroyed the shallow epicontinental sea habitat of the rugosa by intense wave action. The skeletal debris was transported inland and deposited unconformably on the lime mud of the carbonate platform. When conditions normalized, lime mud was deposited onto the fossiliferous shale unit.
Keywords: growth, cycles, paleoecology, Devonian Rugosa, monthly, corallite, water, population, skeletal debris